PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN ASING TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Karima, Naila (Widya Warta, 2014)
This study aimed to examine the effect of managerial ownership, institutional ownership, and foreign ownership toward CSR disclosure in annual reports with the type of industry, profitability, and leverage as a control variable. The population of this study included all public companies listed in Indonesia Stock Exchange of 2009-2011. The sample was obtained using purposive sampling technique. It comprised 32 public companies. The data analysis was conducted by making use of multiple linear regression method. The results showed that managerial ownership significantly influenced CSR disclosure on publiclytraded companies listed in the Stock Exchange of 2009-2011, so H1 is accepted. While, institutional ownership and foreign ownership had no significant effect on the disclosure of CSR in the goingpublic companies listed in the Stock Exchange of 2010-2012, so H2 and H3 are not accepted..Â